THE ROLE OF THE MEDIA ON THE POLITICAL AGENDA SETTING: THE 2019 HONG KONG PROTESTS CASE STUDY - Martins Barros, Gabriella Campos (2022)
Hong Kong caught the attention of international media coverage during the mass mobilisation against the implementation of the Bill of Extradition in 2019. If approved, the law enforcement stated that police officers would be able to extradite or detain a person arrested outside mainland to face trial in mainland China. With the spread of information and communication technologies, the media started to be more effective in conveying events and at the same time at creating a perception. Undoubtedly, the media, known as the Fourth State, is the most important building block in shaping people’s perceptions in the 21st century (Cooke, 2019). Therefore, this paper focuses on the role of the media as a tool for political change. The authors use the case of the 2019 Hong Kong Bill of Extradition protests, a non-democratic political regime, to understand how the media is fundamental for political debate and political change. DOI: https://doi.org/10.29327/252935.13.1-3